2001
DOI: 10.1097/00124509-200109000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Successful Electroconvulsive Therapy in an Elderly Man with Severe Thrombocytopenia: Case Report and Literature Review

Abstract: Electroconvulsive therapy (ECT) is a safe and effective treatment for depression. Furthermore, modifications to ECT have made it a safe procedure for patients who were previously thought to be too ill or old to undergo the stress of convulsions. Little is known, however, of the safety of performing ECT on patients with severe thrombocytopenia. Such patients may be at increased risk for hemorrhagic complications due to the procedure. In this article, we describe the case of a 74-year-old man with major depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This 64-yearold woman had platelet counts between 7 and 38 K/cm 3 . A more recent case report from 2001 demonstrated that a 74-year-old man with severe depression and myelodysplastic syndrome successfully underwent a course of ECT for a total of nine treatments without complication [39]. The patient's platelet count was below 20 K/cm 3 in eight of the treatments, and received pretreatment transfusions of platelets before each treatment.…”
Section: Hematology and Coagulationmentioning
confidence: 99%
“…This 64-yearold woman had platelet counts between 7 and 38 K/cm 3 . A more recent case report from 2001 demonstrated that a 74-year-old man with severe depression and myelodysplastic syndrome successfully underwent a course of ECT for a total of nine treatments without complication [39]. The patient's platelet count was below 20 K/cm 3 in eight of the treatments, and received pretreatment transfusions of platelets before each treatment.…”
Section: Hematology and Coagulationmentioning
confidence: 99%
“…For the same reasons, insertion of a palliative oesophageal stent was not possible. There are only a few reports in the literature that deal with invasive procedures in severely thrombocytopenic patients [9,10], and in general a platelet count around 50 3 10 9 /l is recommended. In a series from New York, uncorrectable coagulopathy was cited as an absolute contraindication to PEG insertion [11].…”
Section: Discussionmentioning
confidence: 99%